The survivors [large type] - Schulman, Alex, 1976- (Random House Large Print, 2021)
"Three estranged brothers return to the lakeside cottage where, over two decades before, an unspeakable accident forever altered their family. There is Nils, the oldest, who couldn't escape his suffocating home soon enough, and Pierre, the youngest, easily bullied and quick to lash out. And then there is Benjamin, always the family's nerve center, perpetually on the look-out for triggers and trap doors...By brilliantly dissecting a mind unravelling in the wake of tragedy, Alex Schulman reveals the ways in which our deepest loyalties leave us open to the greatest betrayals"--